HOMONYMS IN ARABIC RHETORIC - N.M. Mullasadikova (Zeta Repository, 2023)
In Arabic stylistics, the use of words in various decorations is considered the main theme of the science of eloquence. This article pro vides information about the artistic design of Arabic poetry and its types, as well as information about the concept of verbal decoration and its types. In particular, the concepts of " are included in a series of verbal decorations, are described in detail in the text about their types and conditions of use, and examples are given.